Addressing Longevity Heterogeneity in Pension Scheme Design and Reform - Mercedes Ayuso; Jorge Miguel Bravo; Robert Holzmann (Institute for the Study of Labor (IZA), 2016)
This paper demonstrates that the link between heterogeneity in longevity and lifetime income across countries is mostly high and often increasing; that it translates into an implicit tax/subsidy, with rates reaching 20 percent and higher in some countries; that such rates risk perverting redistributive objectives of pension schemes and distorting individual lifecycle labor supply and savings decisions; and that this in turn risks invalidating current reform approaches of a closer contribution-benefit link and life expectancy-indexed retirement age. All of this calls for mechanisms that neutralize or at least significantly reduce the effects of heterogeneity in longevity through changes in pension design. The paper suggests and explores a number of interventions in the accumulation, benefit determination, and disbursement stages. Among the explored approaches, a two-tier contribution structure seems promising, as a moderate social contribution rate that is already proportionally allocated to the average contribution base is able to broadly compensate for empirically established heterogeneity in the life expectancy/lifetime income relationship.
Keywords: D9; G22; H55; J13; J14; J16; 330; defined contribution scheme; two-tier contribution structure; proxied life expectancy; tax/subsidy structure